Thiamin biosynthesis in Saccharomyces cerevisiae. Origin of carbon-2 of the thiazole moiety. - White, R L (1979)
Radioactivity from [2-14C]glycine enters C-2 of the thiazole moiety of thiamin and no other site, in Saccharomyces cerevisiae (strains A.T.C.C. 24903 and 39916, H.J. Bunker). Radioactivity from L-[Me-14C]methionine or from DL-[2-14C]tyrosine does not enter thiamin.